Nonmotility and phagocytic resistance of Pseudomonas aeruginosa isolates from chronically colonized patients with cystic fibrosis. - Mahenthiralingam, E (1994)
Although Pseudomonas aeruginosa chronically colonizes most older patients with cystic fibrosis (CF), bacterial features responsible for its persistence are understood poorly. We observed that many P. aeruginosa isolates from chronically colonized patients were nonmotile and resistant to phagocytosis by macrophages. P. aeruginosa isolates were collected from 20 CF patients for up to 10 years. Isolates from early colonization were highly motile and expressed both flagellin and pilin. However, many isolates from chronically colonized patients lacked flagellin expression and were nonmotile; a total of 1,030 P. aeruginosa CF isolates were examined, of which 39% were nonmotile. Moreover, sequential isolates recovered from several of the CF patients were consistently nonmotile for up to 10 years. Lack of motility was rare among environmental isolates (1.4%) and other clinical isolates (3.7%) of P. aeruginosa examined. Partial complementation of motility in nonmotile P. aeruginosa isolates was achieved by introduction of extra copies of the rpoN locus carried on plasmid pPT212, indicating that the alternate sigma factor, RpoN, may be involved in the coordinate regulation of virulence factors during CF infection. We hypothesize that the nonmotile phenotype may provide P. aeruginosa a survival advantage in chronic CF infection by enabling it to resist phagocytosis and conserve energy.